(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Bronchial asthma (BA) remains one of the most prevalent chronic respiratory diseases worldwide, affecting approximately 300 million people. Despite advances in pharmacological treatment and patient education, acute exacerbations remain a significant clinical and socioeconomic problem. One of the most frequent triggers of asthma exacerbations is infection of the upper or lower respiratory tract, both viral and bacterial. Viral infections - especially those caused by rhinoviruses, influenza, and respiratory syncytial virus - are known to enhance airway inflammation and hyperresponsiveness, resulting in worsening of asthma control. The present study aimed to evaluate the impact of acute infectious diseases on the frequency and severity of asthma exacerbations among adult patients, and to analyze the relationship between specific pathogens and the clinical course of bronchial asthma.